Accountability, Transparency, and Employee Performance in Organizational Asset Management in Buddhist Religious Organizations: Evidence from the Regional Office of the Ministry of Religion of South Sumatra Province - Wiswadas, Wiswadas; Sobri, Kgs. M.; Alfatih, Andy; Alamsyah, Alamsyah (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2023)
This study aimed to examine the effect of accountability and transparency on employee performance in Buddhist. The study employed quantitative design with a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to analyze data collected from 170 respondents. The findings showed that accountability and transparency had a positive and significant effect on employee performance in Buddhist organizations. This result provide important implications for organizational management and the need to foster a culture of accountability and transparency to enhance employee performance. The study also has practical implications for organizational leaders and policy makers who seek to improve the effectiveness of their organizations. By promoting accountability and transparency, organizations can build trust with stakeholders and enhance their reputation, which can lead to increased support and resources.